Polymer, method for preparing polymer and thermoplastic resin composition comprisign the same

KR103017876B1Active Publication Date: 2026-09-11LG CHEM LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
KR1020200163057
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-11-27
Publication Date
2026-09-11
Estimated Expiration
2040-11-27
Patent Text Reader

Abstract

The present invention relates to a polymer comprising (meth)acrylate-based monomer units; vinyl aromatic-based monomer units; and vinyl cyanide-based monomer units, wherein the vinyl aromatic-based monomer units are present in an amount of 51 to 63 weight%, a method for manufacturing the same, and a thermoplastic resin composition comprising the same.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to a polymer, a method for manufacturing the same, and a thermoplastic resin composition containing the same, wherein the invention relates to a polymer having excellent chemical resistance and processability, a method for manufacturing the same, and a thermoplastic resin composition containing the same. Background Technology

[0003] Polycarbonate, polymethyl methacrylate, polystyrene, and styrene / acrylonitrile polymers are primarily used as transparent materials. Among these, polycarbonate has excellent impact resistance and transparency, but its poor processability makes it difficult to manufacture complex products, and its chemical resistance is not excellent. Polymethyl methacrylate is widely used as an optical material due to its excellent optical properties, but its impact resistance and chemical resistance are not excellent. Polystyrene and styrene / acrylonitrile polymers do not have excellent impact resistance and chemical resistance.

[0004] To overcome these drawbacks, a diene graft polymer comprising a butadiene rubbery polymer grafted with (meth)acrylate monomer units, vinyl aromatic monomer units, and vinyl cyanide units was developed, but it could not be applied to medical and cosmetic products because it did not have excellent chemical resistance due to the (meth)acrylate monomer units.

[0005] Accordingly, there is a need for the development of a transparent material, namely a transparent non-graft polymer, which can compensate for the disadvantages of the aforementioned diene-based graft polymer and has excellent transparency, processability, and chemical resistance. Prior art literature

[0007] KR2013-0075793A The problem to be solved

[0008] The problem that the present invention aims to solve is to provide a polymer with excellent transparency, processability, and chemical resistance. means of solving the problem

[0010] To solve the above-mentioned problem, the present invention provides a polymer comprising (meth)acrylate-based monomer units; vinyl aromatic-based monomer units; and vinyl cyanide-based monomer units, wherein the vinyl aromatic-based monomer units are included in an amount of 51 to 63 weight%.

[0011] In addition, the present invention provides a method for producing a polymer comprising the step of introducing a (meth)acrylate-based monomer, a vinyl aromatic-based monomer, and a vinyl cyanide-based monomer into a reactor to polymerize, wherein the vinyl aromatic-based monomer is introduced in an amount of 50.5 to 63.0 parts by weight per 100 parts by weight of the total of the vinyl aromatic-based monomer, the (meth)acrylate-based monomer, and the vinyl cyanide-based monomer. Effects of the invention

[0013] The polymer according to the present invention can achieve excellent transparency, processability, and chemical resistance. In addition, a thermoplastic resin composition comprising the polymer according to the present invention can achieve significantly excellent injection moldability. Specific details for implementing the invention

[0015] Hereinafter, the present invention will be described in more detail to aid in understanding the invention.

[0016] Terms and words used in this specification and claims shall not be interpreted as being limited to their ordinary or dictionary meanings, but shall be interpreted in a meaning and concept consistent with the technical spirit of the invention, based on the principle that the inventor can appropriately define the concept of the terms to best describe his invention.

[0018] The term '(meth)acrylonitrile-based monomer unit' used in the present invention may be a unit derived from a (meth)acrylonitrile-based monomer. The (meth)acrylonitrile-based monomer is C1 to C 10 It may be an alkyl (meth)acrylate monomer, and C1 to C 10The alkyl (meth)acrylate monomer may be one or more selected from the group consisting of methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, heptyl (meth)acrylate, hexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, and decyl (meth)acrylate, among which methyl methacrylate is preferred.

[0020] The term 'vinyl aromatic monomer unit' used in the present invention may be a unit derived from a vinyl aromatic monomer unit. The vinyl aromatic monomer unit may refer to one or more selected from the group consisting of styrene, α-methyl styrene, p-methyl styrene, 2,4-dimethyl styrene, 4-fluorostyrene, 4-chlorostyrene, 2-chlorostyrene, 4-bromostyrene, and 2-bromostyrene. Styrene is preferred as the vinyl aromatic monomer. The unit derived from the vinyl aromatic monomer may be a vinyl aromatic monomer unit.

[0022] The term 'vinyl cyanide monomer' used in the present invention may refer to one or more selected from the group consisting of acrylonitrile, methacrylonitrile, 2-ethyl-acrylonitrile, and 2-chloroacrylonitrile. Acrylonitrile is preferred as the vinyl cyanide monomer. A unit derived from the vinyl cyanide monomer may be a vinyl cyanide monomer unit.

[0024] In the present invention, the weight of the monomer units included in the polymer can be measured by elemental analysis. Specifically, an elemental analyzer (Thermo Scientific's FLASH 2000) can be used. Among the elements measured by the elemental analyzer, the content of 'N' was analyzed to determine the content of vinyl cyanide-based monomer units (weight%), and the content of 'O' was analyzed to determine the content of (meth)acrylate-based monomer units (weight%). Then, the remaining content obtained by subtracting the content of vinyl cyanide-based monomer units and (meth)acrylate-based monomer units (weight%) from 100 was determined as the content of vinyl aromatic-based monomer units.

[0026] The term 'weight-average molecular weight' used in the present invention can be measured using gel permeation chromatography. Specifically, the polymer can be dissolved in tetrahydrofuran at 0.1 to 0.2 wt%, the tetrahydrofuran can be stabilized at a flow rate of 1 ml, and 100 µl can be injected into a column at 40 ℃, and the value obtained through the 2414 Refractive Index DETECTOR (manufacturer: Waters) mounted on the Alliance® HPLC - e2695 Separations Module (manufacturer: Waters) can be measured by analyzing the value.

[0028] The term 'refractive index' used in the present invention refers to the absolute refractive index of a material, and the refractive index can be recognized as the ratio of the velocity of electromagnetic radiation in free space to the velocity of electromagnetic radiation within the material. In this case, the radiation may be visible light with a wavelength of 450 nm to 680 nm, and specifically, may be visible light with a wavelength of 589.3 nm. The refractive index can be measured by a known method, namely an Abbe refractometer.

[0029] More specifically, after flattening the polymer to a thickness of 0.04 mm using a hot press at 245 ℃, using visible light with a wavelength of 589.3 nm at 25 ℃, Reichert TM Abbe TM Mark III TM Refractometer (Manufacturer: Reichert) TM It can be measured as 1310488M).

[0031] The term 'initiator' used in the present invention refers to 2,5-dimethyl-2,5-di(t-butylperoxy)hexane, di(t-butylperoxy-isopropyl)benzene, t-butyl cumyl peroxide, di-(t-amyl)-peroxide, dicumyl peroxide, butyl 4,4-di(t-butylperoxy)valerate, t-butylperoxybenzoate, 2,2-di(t-butylperoxy)butane, t-amyl peroxy-benzoate, t-butylperoxy-acetate, t-butylperoxy-(2-ethylhexyl)carbonate, t-butylperoxyisopropyl carbonate, t-butylperoxy-3,5,5-trimethyl-hexanoate, 1,1-di(t-butylperoxy)cyclohexane, t-amyl peroxyacetate, It may be one or more selected from the group consisting of t-amylperoxy-(2-ethylhexyl)carbonate, 1,1-di(t-butylperoxy)-3,5,5-trimethylcyclohexane, 1,1-di(t-amylperoxy)cyclohexane, t-butyl-monoperoxy-maleate, and 1,1'-azodi(hexahydrobenzonitrile), among which dicumyl peroxide is preferred.

[0033] The term 'diene-based rubbery polymer' used in the present invention may be a synthetic rubber prepared by crosslinking a diene-based monomer or a diene-based monomer with a monomer capable of polymerizing the diene-based monomer. The diene-based monomer may be one selected from the group consisting of 1,3-butadiene, isoprene, chloroprene, and piperylene, among which 1,3-butadiene is preferred. Here, the monomer capable of polymerizing the diene-based monomer may be a vinyl aromatic monomer.

[0035] The term 'average particle size' used in the present invention can be measured using the dynamic light scattering method, and specifically using the Nicomp 380 instrument of Particle Sizing Systems. In the present invention, the average particle size may refer to the arithmetic mean particle size in the particle size distribution measured by the dynamic light scattering method, that is, the average particle size of the scattering intensity distribution.

[0036] The term 'average particle size' used in the present invention can be measured using a transmission electron microscope (TEM).

[0038] 1. Polymer

[0039] A polymer according to one embodiment of the present invention comprises (meth)acrylate-based monomer units; vinyl aromatic-based monomer units; and vinyl cyanide-based monomer units, wherein the vinyl aromatic-based monomer units are included in an amount of 51 to 63 weight%.

[0041] The above polymer may contain vinyl aromatic monomer units in an amount of 51 to 63 weight%, preferably 53 to 62 weight%. If the above range is satisfied, excellent transparency and processability can be achieved while minimizing the decrease in chemical resistance caused by (meth)acrylate monomer units. However, if vinyl aromatic monomer units are included in an amount less than the above range, chemical resistance decreases. If vinyl aromatic monomer units are included in an amount exceeding the above range, the content of vinyl aromatic monomer units of the diene rubbery polymer included in the graft polymer must be increased to maintain the transparency of the thermoplastic resin composition. However, in this case, the diene rubbery polymer loses its rubber properties, so the impact resistance of the thermoplastic resin molded article may be significantly reduced. In addition, if the composition of the diene-based rubbery polymer included in the graft polymer is not controlled in order to maintain impact resistance, the transparency of the thermoplastic resin molded article may be significantly reduced.

[0043] The above polymer may contain (meth)acrylate-based monomer units in an amount of 30 to 45 weight%, preferably 31 to 42 weight%. If the above range is satisfied, excellent transparency can be achieved while minimizing the decrease in chemical resistance caused by (meth)acrylate-based monomer units.

[0045] The above polymer may contain vinyl cyanide-based monomer units in an amount of 2 to 12 weight%, preferably 5 to 10 weight%. If the above range is satisfied, the yellowing caused by the vinyl cyanide-based monomer units is minimized, and the chemical resistance of the polymer can be improved.

[0047] The above polymer may have a weight-average molecular weight of 100,000 to 200,000 g / mol, preferably 130,000 to 160,000 g / mol. When the above range is satisfied, the polymer has the advantage of improved chemical resistance while achieving excellent processability and impact resistance.

[0049] The above polymer may have a refractive index of 1.53 to 1.57, preferably 1.54 to 1.56. If the above range is satisfied, the chemical resistance and processability of the polymer can be improved by the composition of the monomer units.

[0051] The above polymer may have a flow index of 40 to 60 g / 10 min, preferably 45 to 55 g / min, measured under conditions of 220 ℃ and 10 kg in accordance with ASTM D1238. If the above range is satisfied, processability, particularly injection molding characteristics, can be improved.

[0053] The above polymer may be a non-graft polymer.

[0055] 2. Method for manufacturing a polymer

[0056] A method for manufacturing a polymer according to another embodiment of the present invention comprises the step of polymerizing by introducing a (meth)acrylate-based monomer, a vinyl aromatic-based monomer, and a vinyl cyanide-based monomer into a reactor, wherein the vinyl aromatic-based monomer is introduced in an amount of 50.5 to 63.0 parts by weight relative to 100 parts by weight of the total of the vinyl aromatic-based monomer, the (meth)acrylate-based monomer, and the vinyl cyanide-based monomer.

[0058] For every 100 parts by weight of the sum of the vinyl aromatic monomer, (meth)acrylate monomer, and vinyl cyanide monomer, the vinyl aromatic monomer may be introduced into the reactor in an amount of 50.5 to 63.0 parts by weight, preferably 50.5 to 61.0 parts by weight. If the above-described range is satisfied, excellent transparency and processability can be achieved while minimizing the decrease in chemical resistance caused by (meth)acrylate monomer units. However, if the vinyl aromatic monomer is included in an amount less than the above-described range, chemical resistance decreases. If the vinyl aromatic monomer is included in an amount exceeding the above-described range, the content of vinyl aromatic monomer units of the diene rubbery polymer included in the graft polymer must be increased to maintain the transparency of the thermoplastic resin composition. However, in this case, the diene rubbery polymer loses its rubber properties, so the impact resistance of the thermoplastic resin molded article may be significantly reduced. In addition, if the composition of the diene-based rubbery polymer included in the graft polymer is not controlled in order to maintain impact resistance, the transparency of the thermoplastic resin molded article may be significantly reduced.

[0060] For every 100 parts by weight of the sum of the vinyl aromatic monomer, (meth)acrylate monomer, and vinyl cyanide monomer, 30 to 45 parts by weight, preferably 32 to 43 parts by weight, of the (meth)acrylate monomer can be introduced into the reactor. If the above-mentioned range is satisfied, excellent transparency can be achieved while minimizing the decrease in chemical resistance caused by the (meth)acrylate monomer unit.

[0062] For every 100 parts by weight of the sum of the vinyl aromatic monomer, (meth)acrylate monomer, and vinyl cyanide monomer, the vinyl cyanide monomer may be introduced into the reactor in an amount of 2 to 12 parts by weight, preferably 5 to 10 parts by weight. If the above-described range is satisfied, the chemical resistance of the polymer can be improved while minimizing the yellowing caused by the vinyl cyanide monomer units.

[0064] The above polymerization may be a solution polymerization capable of producing a high-purity product, and preferably, it may be a continuous solution polymerization capable of producing a high-purity product and improving manufacturing efficiency by having a high polymerization conversion rate.

[0066] During the above polymerization, an initiator and a molecular weight regulator may be further added to the reactor.

[0067] For every 100 parts by weight of the sum of the vinyl aromatic monomer, (meth)acrylate monomer, and vinyl cyanide monomer, an initiator can be introduced into the reactor in an amount of 0.005 to 0.050 parts by weight, preferably 0.01 to 0.03 parts by weight. If the above-described range is satisfied, a transparent polymer with a high polymerization conversion rate can be produced.

[0068] For every 100 parts by weight of the sum of the vinyl aromatic monomer, (meth)acrylate monomer, and vinyl cyanide monomer, a molecular weight regulator may be added to the reactor in an amount of 0.05 to 0.30 parts by weight, preferably 0.1 to 0.2 parts by weight. If the above-described range is satisfied, a polymer with excellent processability and impact resistance can be produced.

[0070] A method for manufacturing a polymer according to another embodiment of the present invention may perform a devolatilization process at 220 to 250°C and 20 torr or less to remove unreacted monomers and solvent, and preferably at 230 to 240°C and 20 torr or less. By performing the devolatilization process under the above conditions, a polymer with low residue can be manufactured.

[0072] 3. Thermoplastic resin composition

[0073] A method for manufacturing a polymer according to another embodiment of the present invention includes a polymer according to one embodiment of the present invention.

[0074] The above thermoplastic resin composition may include a graft polymer comprising a diene-based rubbery polymer grafted with vinyl aromatic monomer units, (meth)acrylate monomer units, and vinyl cyanide monomer units.

[0075] The above-mentioned diene-based rubbery polymer may have an average particle size of 50 to 500 nm, preferably 100 to 450 nm. If the above conditions are satisfied, a graft polymer with excellent impact resistance and surface gloss properties can be produced.

[0076] The above diene-based rubbery polymer may be one or more selected from the group consisting of butadiene rubbery polymers and styrene / butadiene rubbery polymers, and the styrene / butadiene rubbery polymer may be prepared by crosslinking styrene and butadiene in a weight ratio of 37:63 to 50:50, preferably 40:60 to 50:50. If the above conditions are satisfied, a rubbery polymer having excellent chemical resistance and impact resistance can be produced.

[0078] The difference in refractive index between the graft polymer and the polymer according to one embodiment of the present invention may be 0.001 or less, and preferably 0.0003 or less. If the difference in refractive index between the graft polymer and the polymer according to one embodiment of the present invention is minimized, a thermoplastic resin composition with superior transparency can be produced.

[0080] The above thermoplastic resin composition may include the polymer and the graft polymer in a weight ratio of 70:30 to 40:60, and preferably in a weight ratio of 60:40 to 50:50. If the above conditions are satisfied, a molded article with excellent impact resistance and chemical resistance can be manufactured.

[0082] Hereinafter, embodiments of the present invention are described in detail so that those skilled in the art can easily implement the invention. However, the present invention may be embodied in various different forms and is not limited to the embodiments described herein.

[0084] Example 1

[0085] <Manufacture of Polymers>

[0086] A polymerization solution was prepared comprising 10 parts by weight of toluene, 42.1 parts by weight of methyl methacrylate, 50.9 parts by weight of styrene, 7 parts by weight of acrylonitrile, 0.015 parts by weight of dicumyl peroxide, and 0.175 parts by weight of t-butyl mercaptan.

[0087] The above polymerization solution was fed into a continuous polymerization reactor set at 145°C at a rate of 10 kg / L to obtain a polymer. The polymer was transferred to a volatilization tank, and unreacted monomers and solvent were removed under conditions of 230°C and 20 torr to produce polymer pellets.

[0089] <Preparation of Thermoplastic Resin Composition>

[0090] A thermoplastic resin composition was prepared by mixing 50 parts by weight of the above polymer pellets, 50 parts by weight of a graft polymer (styrene-butadiene rubbery polymer grafted with methyl methacrylate units, styrene units, and acrylonitrile units (styrene content in the rubbery polymer: 40 wt%, average particle size of the rubbery polymer: 310 nm), refractive index: 1.5455), 1 part by weight of ethylenebisstearamide, and 0.5 parts by weight of an antioxidant (AO-11B of Songwon Industry).

[0092] Example 2

[0093] <Manufacture of Polymers>

[0094] A polymerization solution was prepared comprising 10 parts by weight of toluene, 36.7 parts by weight of methyl methacrylate, 56.3 parts by weight of styrene, 7 parts by weight of acrylonitrile, 0.015 parts by weight of dicumyl peroxide, and 0.155 parts by weight of t-butyl mercaptan.

[0095] The above polymerization solution was fed into a continuous polymerization reactor set at 145°C at a rate of 10 kg / L to obtain a polymer. The polymer was transferred to a volatilization tank, and unreacted monomers and solvent were removed under conditions of 230°C and 20 torr to produce polymer pellets.

[0097] <Preparation of Thermoplastic Resin Composition>

[0098] A thermoplastic resin composition was prepared by mixing 50 parts by weight of the above polymer pellets, 50 parts by weight of a graft polymer (styrene-butadiene rubbery polymer grafted with methyl methacrylate units, styrene units, and acrylonitrile units (styrene content in the rubbery polymer: 45 wt%, average particle size of the rubbery polymer: 310 nm), refractive index: 1.5493), 1 part by weight of ethylenebisstearamide, and 0.5 parts by weight of an antioxidant (AO-11B of Songwon Industry).

[0100] Example 3

[0101] <Manufacture of Polymers>

[0102] A polymerization solution was prepared comprising 10 parts by weight of toluene, 32.50 parts by weight of methyl methacrylate, 60.5 parts by weight of styrene, 7 parts by weight of acrylonitrile, 0.015 parts by weight of dicumyl peroxide, and 0.14 parts by weight of t-butyl mercaptan.

[0103] The above polymerization solution was fed into a continuous polymerization reactor set at 145°C at a rate of 10 kg / L to obtain a polymer. The polymer was transferred to a volatilization tank, and unreacted monomers and solvent were removed under conditions of 230°C and 20 torr to produce polymer pellets.

[0105] <Preparation of Thermoplastic Resin Composition>

[0106] A thermoplastic resin composition was prepared by mixing 50 parts by weight of the above polymer pellets, 50 parts by weight of a graft polymer (styrene-butadiene rubbery polymer grafted with methyl methacrylate units, styrene units, and acrylonitrile units (styrene content in the rubbery polymer: 50 wt%, average particle size of the rubbery polymer: 310 nm), refractive index: 1.5525), 1 part by weight of ethylenebisstearamide, and 0.5 parts by weight of an antioxidant (AO-11B of Songwon Industry).

[0108] Comparative Example 1

[0109] <Manufacture of Polymers>

[0110] A polymerization solution was prepared comprising 10 parts by weight of toluene, 74.3 parts by weight of methyl methacrylate, 18.7 parts by weight of styrene, 7 parts by weight of acrylonitrile, 0.015 parts by weight of dicumyl peroxide, and 0.55 parts by weight of t-butyl mercaptan.

[0111] The above polymerization solution was fed into a continuous polymerization reactor set at 145°C at a rate of 10 kg / L to obtain a polymer. The polymer was transferred to a volatilization tank, and unreacted monomers and solvent were removed under conditions of 230°C and 20 torr to produce polymer pellets.

[0113] <Preparation of Thermoplastic Resin Composition>

[0114] A thermoplastic resin composition was prepared by mixing 50 parts by weight of the above polymer pellets, 50 parts by weight of a graft polymer (TR550 of LG Chem, a butadiene rubbery polymer grafted with methyl methacrylate units, styrene units, and acrylonitrile units (average particle size: 310 nm), refractive index: 1.5156), 1 part by weight of ethylenebisstearamide, and 0.5 parts by weight of an antioxidant (AO-11B of Songwon Industry).

[0116] Comparative Example 2

[0117] <Manufacture of Polymers>

[0118] A polymerization solution was prepared comprising 20 parts by weight of toluene, 74.3 parts by weight of methyl methacrylate, 18.7 parts by weight of styrene, 7 parts by weight of acrylonitrile, 0.015 parts by weight of dicumyl peroxide, and 0.15 parts by weight of t-butyl mercaptan.

[0119] The above polymerization solution was fed into a continuous polymerization reactor set at 145°C at a rate of 10 kg / L to obtain a polymer. The polymer was transferred to a volatilization tank, and unreacted monomers and solvent were removed under conditions of 230°C and 20 torr to produce polymer pellets.

[0121] <Preparation of Thermoplastic Resin Composition>

[0122] It was manufactured using the same method as Comparative Example 1.

[0124] Comparative Example 3

[0125] <Manufacture of Polymers>

[0126] A polymerization solution was prepared comprising 10 parts by weight of toluene, 47.9 parts by weight of methyl methacrylate, 45.1 parts by weight of styrene, 7 parts by weight of acrylonitrile, 0.015 parts by weight of dicumyl peroxide, and 0.195 parts by weight of t-butyl mercaptan.

[0127] The above polymerization solution was fed into a continuous polymerization reactor set at 145°C at a rate of 10 kg / L to obtain a polymer. The polymer was transferred to a volatilization tank, and unreacted monomers and solvent were removed under conditions of 230°C and 20 torr to produce polymer pellets.

[0129] <Preparation of Thermoplastic Resin Composition>

[0130] A thermoplastic resin composition was prepared by mixing 50 parts by weight of the above polymer pellets, 50 parts by weight of a graft polymer (styrene-butadiene rubbery polymer grafted with methyl methacrylate units, styrene units, and acrylonitrile units (styrene content in the rubbery polymer: 35 wt%, average particle size of the rubbery polymer: 310 nm), refractive index: 1.5412), 1 part by weight of ethylenebisstearamide, and 0.5 parts by weight of an antioxidant (A0-11B of Songwon Industry).

[0132] Comparative Example 4

[0133] <Manufacture of Polymers>

[0134] A polymerization solution was prepared comprising 10 parts by weight of toluene, 27.5 parts by weight of metal methacrylate, 65.5 parts by weight of styrene, 7 parts by weight of acrylonitrile, 0.015 parts by weight of dicumyl peroxide, and 0.125 parts by weight of t-butyl mercaptan.

[0135] The above polymerization solution was fed into a continuous polymerization reactor set at 145°C at a rate of 10 kg / L to obtain a polymer. The polymer was transferred to a volatilization tank, and unreacted monomers and solvent were removed under conditions of 230°C and 20 torr to produce polymer pellets.

[0137] <Preparation of Thermoplastic Resin Composition>

[0138] A thermoplastic resin composition was prepared by mixing 50 parts by weight of the above polymer pellets, 50 parts by weight of a graft polymer (styrene-butadiene rubbery polymer grafted with methyl methacrylate units, styrene units, and acrylonitrile units (styrene content in the rubbery polymer: 55 wt%, average particle size of the rubbery polymer: 310 nm), refractive index: 1.5566), 1 part by weight of ethylenebisstearamide, and 0.5 parts by weight of an antioxidant (A0-11B of Songwon Industry).

[0140] Experimental Example 1

[0141] The physical properties of the polymers of the examples and comparative examples were evaluated using the methods described below, and the results are listed in Tables 1 and 2.

[0143] (1) Content of monomer units in the polymer (weight%): Measured by elemental analysis using an elemental analyzer (Thermo Scientific FLASH 2000). Specifically, the content of 'N' was analyzed to determine the content of acrylonitrile units (weight%), and the content of 'O' was analyzed to determine the content of methyl methacrylate units (weight%). Then, the remaining content after subtracting the content of acrylonitrile units and methyl methacrylate units (weight%) from 100 was determined as the content of styrene units (weight%).

[0144] (2) Refractive index: After flattening the polymer pellets to a thickness of 0.04 mm using a hot press at 245 ℃, the Reichert level was measured using visible light with a wavelength of 589.3 nm at 25 ℃. TM Abbe TM Mark III TM Refractometer (Manufacturer: Reichert) TM It can be measured as 1310488M).

[0145] (3) Weight-average molecular weight (g / mol): After dissolving the polymer in tetrahydrofuran at 0.1 to 0.2 wt% and stabilizing the tetrahydrofuran at a flow rate of 1 ml, 100 µl was injected into a column at 40 ℃, and the value obtained through the 2414 Refractive Index DETECTOR (manufacturer: Waters) mounted on the Alliance® HPLC - e2695 Separations Module (manufacturer: Waters) was analyzed and measured.

[0146] (4) Melt flow index (g / 10 min): Measured according to ASTM D1238 under conditions of 220 ℃ and 10 kg.

[0147] (5) Haze (%): A gloss specimen (thickness: 1 / 8 inch) was measured using a haze meter (SUGA Test Instrument HZ-V3) in accordance with ASTM D1003.

[0148] (6) b value: A gloss specimen (thickness: 1 / 8 inch) was measured using Hunter Lab.

[0150] Experimental Example 2

[0151] The thermoplastic resin compositions of the examples and comparative examples were fed into an extruder (28 Φ) set to 230 ℃ and extruded to produce thermoplastic resin pellets, and the thermoplastic resin pellets were injected to produce specimens. The physical properties of the specimens were measured by the method described below, and the results are listed in Tables 1 and 2 below.

[0153] (1) Transmission (Tt): Transmission of a gloss specimen (thickness: 1 / 8 inch) was measured using a haze meter (SUGA Test Instrument HZ-V3) in accordance with ASTM D1003.

[0154] (2) Haze (%): The haze of a gloss specimen (thickness: 1 / 8 inch) was measured using a haze meter (SUGA Test Instrument HZ-V3) in accordance with ASTM D1003.

[0155] (3) b value: A gloss specimen (thickness: 1 / 8 inch) was measured using Hunter Lab.

[0156] (4) Izod impact strength (kg·cm / cm, 1 / 4 Inch): Measured according to ASTM D256.

[0157] (5) Melt flow index (g / 10 min): Measured according to ASTM D1238 under conditions of 220 ℃ and 10 kg.

[0158] (6) Tensile strength (kg / cm², 1 / 8 inch): Measured according to ASTM D638 under conditions of 50 mm / min.

[0159] (7) Chemical resistance: A specimen prepared according to ASTM D638 was fixed in the center of a jig with 1.0% stress applied, and isopropyl alcohol (concentration: 70%) was applied to the center of the specimen. After 5 hours, the condition of the specimen was evaluated.

[0160] ○: No change, △: Crack occurred, ×: Fracture occurred

[0162] division Example 1 Example 2 Example 3 monomer mixture MMA (Heavyweight Division) 42.1 36.7 32.5 SM (weight part) 50.9 56.3 60.5 AN (parts by weight) 7 7 7 polymer MMA Units (Weight%) 39.1 35.1 31.9 SM Units (Weight%) 53.9 57.9 61.1 AN unit (weight%) 7.0 7.0 7.0 Refractive index 1.5452 1.5490 1.5522 weight-average molecular weight 142,000 145,000 146,000 Liquidity Index 47.7 52.2 52.4 Hayes 0.2 0.2 0.2 b value 0.48 0.49 0.50 Thermoplastic resin composition Transmittance 90.9 90.7 90.7 Hayes 1.8 1.9 2.0 b value 1.7 1.8 1.8 Impact strength 13.5 13.1 12.7 Liquidity Index 4.4 4.7 4.7 tensile strength 341 345 353 Chemical resistance ○ ○ ○

[0163] division Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 monomer mixture MMA (Heavyweight Division) 74.3 74.3 47.9 27.5 SM (weight part) 18.7 18.7 45.1 65.5 AN (parts by weight) 7 7 7 7 polymer MMA Units (Weight%) 68.7 68.7 43.2 27.8 SM Units (Weight%) 24.2 24.2 49.8 65.2 AN unit (weight%) 7.1 7.1 7 7 Refractive index 1.5153 1.5153 1.5409 1.5563 weight-average molecular weight 92,000 145,000 138,000 149,000 Liquidity Index 49.5 10.3 51.2 52.7 Hayes 0.2 0.2 0.2 0.2 b value 0.48 0.52 0.47 0.50 Thermoplastic resin composition Transmittance 91.0 90.5 90.9 90.7 Hayes 1.8 2.0 1.8 2.1 b value 1.7 1.9 1.7 1.8 Impact strength 7.8 14.2 13.7 10.8 Liquidity Index 4.6 2.5 4.6 4.7 tensile strength 412 325 324 381 Chemical resistance × △ △ ○

[0164] Referring to Tables 1 and 2, the thermoplastic resin compositions of Examples 1 to 3, which contain a polymer containing 50.9 to 60.5 wt% of styrene units, exhibited excellent transparency with high transmittance values ​​and low haze values, and did not exhibit yellowness with low b values. Additionally, they had excellent processability with high flow index, and excellent impact resistance and chemical resistance. However, the thermoplastic resin composition of Comparative Example 1, which uses a polymer containing 18.7 wt% of styrene units and a weight-average molecular weight of 92,000 g / mol, showed significantly reduced impact resistance and chemical resistance compared to the thermoplastic resin compositions of Examples 1 to 3.

[0165] The thermoplastic resin composition of Comparative Example 2, which uses a polymer containing 18.7 wt% of styrene units and a weight-average molecular weight of 145,000 g / mol, has a lower flow index compared to the thermoplastic resin compositions of Examples 1 to 3, resulting in significantly reduced processability and reduced chemical resistance.

[0166] The thermoplastic resin composition of Comparative Example 3, which contains 49.8 wt% of styrene units and has a weight-average molecular weight of 138,000 g / mol, has reduced chemical resistance compared to the thermoplastic resin compositions of Examples 1 to 3.

[0167] The thermoplastic resin composition of Comparative Example 4, which contains 65.2 wt% of styrene units and has a weight-average molecular weight of 149,000 g / mol, utilized a graft polymer prepared from a styrene / butadiene rubbery polymer containing 55 wt% of styrene monomer units to maintain transparency. However, the styrene / butadiene rubbery polymer of the graft polymer contained an excessive amount of styrene units, thereby losing its rubbery properties. Consequently, the impact resistance of the thermoplastic resin composition of Comparative Example 4 was significantly reduced compared to the thermoplastic resin compositions of Examples 1 to 3.

Claims

Claim 1 A non-graft polymer comprising (meth)acrylate monomer units; vinyl aromatic monomer units; and vinyl cyanide monomer units, wherein the (meth)acrylate monomer units are included in an amount of 30 to 45 weight% and the vinyl aromatic monomer units are included in an amount of 51 to 63 weight%. Claim 2 A non-graft polymer according to claim 1, wherein the polymer comprises 53 to 62 weight percent of the vinyl aromatic monomer unit. Claim 3 delete Claim 4 A non-graft polymer according to claim 1, wherein the polymer comprises 31 to 42 weight percent of the (meth)acrylate-based monomer unit. Claim 5 The non-graft polymer of claim 1, wherein the polymer has a weight-average molecular weight of 100,000 to 200,000 g / mol. Claim 6 The non-graft polymer of claim 1, wherein the polymer has a refractive index of 1.53 to 1.

57. Claim 7 The non-graft polymer of claim 1, wherein the polymer has a flow index of 40 to 60 g / 10 min measured under conditions of 220 ℃ and 10 kg in accordance with ASTM D1238. Claim 8 A method for manufacturing a non-graft polymer comprising the step of polymerizing a (meth)acrylate monomer, a vinyl aromatic monomer, and a vinyl cyanide monomer by introducing them into a reactor, wherein, for every 100 parts by weight of the sum of the (meth)acrylate monomer, the vinyl aromatic monomer, and the vinyl cyanide monomer, the (meth)acrylate monomer is introduced in an amount of 30.0 to 45.0 parts by weight and the vinyl aromatic monomer is introduced in an amount of 50.5 to 63.0 parts by weight. Claim 9 A method for producing a non-graft polymer according to claim 8, wherein the vinyl aromatic monomer is added in an amount of 50.5 to 61.0 parts by weight to 100 parts by weight of the sum of the (meth)acrylate monomer, the vinyl aromatic monomer, and the vinyl cyanide monomer. Claim 10 A method for producing a non-graft polymer according to claim 8, wherein the polymerization is a solution polymerization. Claim 11 A thermoplastic resin composition comprising a non-graft polymer according to claim 1. Claim 12 The thermoplastic resin composition of claim 11, wherein the thermoplastic resin composition comprises a graft polymer comprising a diene-based rubbery polymer grafted with vinyl aromatic monomer units, (meth)acrylate monomer units, and vinyl cyanide monomer units. Claim 13 A thermoplastic resin composition according to claim 12, wherein the diene-based rubbery polymer is one or more selected from the group consisting of butadiene rubbery polymers and styrene / butadiene rubbery polymers.

Citation Information

Patent Citations

  • Method for producing thermoplastic copolymer

    JP3664576B2

  • Thermoplastic resin composition with good mechanicalproperties, weatherability and colorability

    KR100828727B1

  • Production of thermoplastic copolymer

    JP1998152504A

  • Thermoplastic resin composition applicable to weatherable and reduced gloss

    KR101339384B1

  • Thermoplastic Resin Composition having Excellent Appearance and Colorability

    KR1020130075793A